Hubungan Iklim Keselamatan Dengan Perilaku Selamat Pada Pekerja - Nafisa, Ghina Safa; Lubis, Siti Rahmah Hidayatullah (Journal of Religion and Public Health, 2023)
AbstractThe industry's high number of work accident cases is generally caused by workers' low awareness of how to behave safely while working. Safety climate is workers' perceptions regarding aspects related to safety in the workplace. This research aims to determine the relationship between safety climate and worker safety behavior. The study design used was cross-sectional with a quantitative approach. The research was conducted in March – June 2022 among field workers in high-risk jobs, with a sample of 124 respondents. Data was collected online and offline using the Accidental Sampling technique. Data analysis used the chi-square statistical test. The research results showed that 52.4% of workers had behaved safely. Variables related to safety behavior are level of education (p= 0.035), priority dimensions and management commitment to safety (p=0.006), empowerment of work safety management (p=0.001), justice of work safety management (p=0.006), and learning communication and innovation (p=0.036). Suggestions that can be given are that companies need to conduct additional workshops with specific themes, create strict sanctions as a form of management commitment, create closed forms for accident investigations, and submit suggestions.Keywords: Safety Climate, Safety Behavior, Workers